Aktivitas Antihiperurisemia dan Evaluasi Sifat Fisik Sediaan Sirup Ekstrak Labu Kuning ( Cucurbita maxima ) - Istianatus Sunnah; Agitya Resti Erwiyani; Mega Silvi Aprilliani; Maryanti Maryanti; Galih Adi Pramana (Indonesian Journal of Pharmacy and Natural Product, 2021)
Konsumsi makanan tinggi purin akan menyebabkan peningkatan kadar asam urat dalam darah. Akibat kadar  asam urat yang tinggi ( hiperurisemia) dan yang tidak terkontrol, akan menyebabkan gangguan pada organ tubuh sehingga timbul penyakit jantung, ginjal maupun Diabetes Mellitus. Allopurinol saat ini masih digunakan sebagai terapi asam urat / gout tetapi memiliki efek samping ruam, gangguan pencernaan, gangguan ginjal dan hati. Tujuan dari penelitian ini untuk mengkaji ekstrak labu kuning yang mengandung flavonoid dan terpenoid dapat digunakan sebagai terapi antihiperurisemia akibat adanya induksi pakan tinggi purin yaitu jus hati dan melinjo (1:1) selama 30 hari. Konsentrasi ekstrak yang digunakan 200 mg/KgBB, 400 mg/KgBB dan 600 mg/KgBB diberikan selama 7 hari dan dibuat sediaan sirup untuk memudahkan penggunaan.  Formulasi sirup diuji sifat fisik dan karakteristik berdasar SNI. Hasil penelitian, menunjukkan bahwa ELBK 600 mg/KgBB  memiliki aktivitas antihiperurisemia sebanding dengan Allopurinol (p value = 0,436 > 0,05), dan peningkatan konsentrasi ELBK memberikan aktivitas yang berbeda  terhadap penurunan kadar asam urat (p value= 0,00). Sediaan formulasi sirup belum memenuhi syarat mutu SNI karena pH masih asam, kadar gula dibawah 65%.Consumption of high purine feeds will cause an increase in uric acid levels in the blood. Due to high uric acid levels (hyperuricemia) and uncontrolled, it will cause disturbances in the body's organs, causing heart disease, kidney disease and Diabetes Mellitus. Allopurinol is used as a therapy for gout but has side effects of rashes, indigestion, kidney and liver disorders. The purpose of this study was to study pumpkin extract containing flavonoids and terpenoids which can be used as antihyperuricemia therapy due to the induction of high-purine feed, are chicken liver juice and melinjo (1: 1) for 30 days in Wistar rats. The concentration of the extract used was 200 mg / KgBW, 400 mg / KgBW and 600 mg / KgBW given for 7 days and a syrup formulation was made for ease of use. The syrup formulation with the ratio of PGA (7.5% and 10%) was tested for physical properties and characteristics based on the SNI quality requirements in the form of organoleptic, pH, specific gravity and viscosity. The results showed that ELBK 600 mg / KgBW had antihyperuricemic activity comparable to Allopurinol (p value = 0.436> 0.05), and increased ELBK concentrations gave different activities to decrease uric acid levels (p value = 0.00). Organoleptically in the form of shape, taste and smell, pumpkin syrup did not differ between groups due to the addition of PGA concentrations. Syrup have  pH 3.8 ± 0.011, BJ 1.260 ± 0.001. The viscosity of the syrup changed with the addition of the PGA concentration with a viscosity of F1 of 2.222 ± 0.001 cps and a viscosity of F 2 of 4.447 ± 0.001 cps. Pumpkin extract has activity in reducing uric acid levels and the syrup formulation does not meet the SNI quality requirements because the pH is still acidic, the sugar content is below 65%.